Development of a Car Battery Monitoring System. - Dusabimana Abel (Kabale University, 2023)
Battery management system (BMS) is an integral part of an automobile. It protects the battery from damage, predicts battery life and maintains the battery in an operational condition. The BMS performs these tasks by integrating one or more of the functions, such as protecting the cell, controlling the charge, determining the state of charge (SOC), the state of health (SOH), and the remaining useful life (RUL) of the battery, cell balancing, as well as monitoring and storing historical data.The purpose of battery level monitoring system is to measure and monitor the fundamental parameters of a rechargeable battery. The parameters that are measured and monitored are the output voltage and current of the battery. The output voltage is used in the real-time calculation of the remaining time before the rechargeable battery is exhausted and in case of malfunction. The monitoring of discharging state of the battery and also the battery voltage value is displayed by using LCD. The GSM module is to be used for communication purpose of sending the message via mobile phone indicating low battery level and then the buzzer is to trigger an alarm. The brain of the system is the microcontroller. The processes are managed by this microcontroller, which provides the data needed to be displayed on the LCD screen.